Rapid biodegradation of glyphosate by plant growth-promoting Ochrobactrum sp. Y3: Degradation kinetics, metabolic pathways and environmental bioremediation - Shichen Dai; Chenxi Yan; Mingqiu Liu; Yuxi Sun; Keyi Wang; Guiling Si; Mohamed A. Ghorab; Shaohua Chen (Journal of Environmental Chemical Engineering, 2026)

Systemic resilience of the urban educational facility system: A spatiotemporal framework coupling chronic stresses and acute shocks - Ziteng Liu; Shichen Zhao; Ze Liu (Sustainable Cities and Society, 2026)

Divergent microplastic assemblages across natural and artificial waters in the Wei River Basin - Yiping Guo; Zhe Liu; Houpu Ren; Zixuan Zhang; Shichen Wei; Guojin Qi; Taishuo Zhang; Rui Wang; Xinyu Xu; Peng Liu; Hanzhong Jia (Journal of Water Process Engineering, 2026)

Synergistic chemiluminescence enhancement by a MOF-derived Co3O4/In2O3 heterojunction for norepinephrine detection - Jinwei Xiao; Yutong Liu; Jiyang Liu; Tsegu Lijalem; Solomon Sime Tessema; Shichen Liu; Jintao Ma; Guobao Xu (Analytica Chimica Acta, 2026)

Evaluating the Performance of Large Language Models for Breast Cancer Patient Education: A Comparative Study - Qingyue Zhang; Qian Yu; Guili Wang; Zijing Zeng; Shichen Liu; Xinyi Rao; Chang Cheng; Xiaoyuan Wang; Liyuan Shi; Shu Wang; Shanshan He; Yan Wang (Journal of Cancer Education, 2026)

Plant litter addition promotes short-term improvement of saline-alkali soils through labile carbon and enzyme activities - Lirong Zhao; Yuyang Kou; Mengqi Zhang; Ni Gao; Ermao Ding; Shichen Wang; Kaiyang Han; Yixuan Liu; Minmin Qiang; Huan Ma; Liping Hu; Jun Meng; et al. (Journal of Soils and Sediments, 2026)

Decreases in yield-scaled reactive nitrogen losses and nitrogen surplus by shifting rice-wheat rotation to ratoon rice mode in Southeast China - Jiarong Liu; Guangbin Zhang; Penghui Jin; Shichen Wang; Keda Jin; Jing Ma; Siyuan Cai; Xu Zhao; Shen Yuan; Shaobing Peng; Hua Xu; Xiaoyuan Yan (Field Crops Research, 2026)

A bHLH transcription factor negatively regulates effective panicle number and grain yield by modulating auxin transport and distribution in rice - Tao Yang; Rui Zhu; Jinlong Li; Yulong Wang; Lei Zhou; Qiaoqiao Zhao; Ningjia Jiang; An Zeng; Yanli Qin; Haixia Liu; Chenyu Xia; Shichen Han; et al. (Molecular Plant, 2026)

Aluminum removal from rare earth element-containing mining wastewater using magnesium–aluminum layered double hydroxides: Effects of aging protocol and anionic species - Shichen Liu; Silin Chen; Huining Zhang; Sili Ren; Wuhui Luo (Journal of Environmental Chemical Engineering, 2026)

Enhanced removal of Cr(VI) from aqueous solution by chitosan-modified MOFs: Insights into performance and mechanism - Shichen Wang; Fanglin Shen; Gang Mi; Yuyang Kou; Ni Gao; Minmin Qiang; Huan Ma; Liping Hu; Mei Su; Yixuan Liu; Ermao Ding; Weibo Shen (Journal of Environmental Chemical Engineering, 2025)

Coral-inferred high seasonal sea surface temperature in the South China Sea at 7.4 thousand years ago - Shichen Tao; Kam-biu Liu; Hongqiang Yan; Min Meng; Chun-Yuan Huang; Chuan-Chou Shen; Huiling Zhang; Kefu Yu; Qi Shi (Earth and Planetary Science Letters, 2025)

The RLI1–OsPUB77–OsBZR3 module mediates the crosstalk between phosphate starvation and brassinosteroid signaling pathways to shape rice shoot architecture - Kai Wang; Peng Yan; Jiangfan Guo; Wei Li; Shichen Zhou; Yijian Liu; Jiming Xu; Yu Liu; Yunrong Wu; Zhongchang Wu; Peng Wang; Chuanzao Mao; et al. (Molecular Plant, 2025)

Synergistic cryoprotection of L-proline and L-phenylalanine by gradient control of ice inhibition and osmolyte pressure regulation - Ningning Peng; Xuan Wang; Xinyu Shi; Shulai Liu; Yuting Ding; Xuxia Zhou; Shichen Zhu (Food Chemistry, 2025)

Experimental and numerical study on flashing jet characteristics in the leakage process of hazardous liquefied gas - Yangshuo Dong; He Liu; Yu Guan; Shichen Tu; Jihai Duan; Chaojie Li (Fuel, 2025)

Pyridine N-dominated multi‑nitrogen species sites synergistically promote efficient photocatalytic H2O2 production - Jiawei Lu; Yu Liu; Shichen Cui; Haijiao Xie; Jianning He; Qingyao Wu (Chemical Engineering Journal, 2025)

Self-reinforced nanoreactor for apoptosis/ferroptosis synergistic therapy of head and neck squamous cell carcinoma - Shichen Zhang; Lei Guo; Yixin Tang; Yixing Wang; Heshi Liu; Chang Liu; Xiuzhang Yan; Congcong Duan; Huanyan Dai; Bing Han; Caina Xu (Chemical Engineering Journal, 2025)

Enrichment of nitrogen and phosphorus by navel orange peel–derived biochars coated with different metal (hydro)oxides for the subsequent immobilization of Cd in soil - Wuhui Luo; Qian Liu; Hongkai Cao; Sili Ren; Meng Zhang; Shichen Liu (Journal of Environmental Management, 2025)

Metal organic frameworks intensify lithium ion conduction and SEI formation inlayed in solid electrolyte facing with lithium metal anode - Shichen Zhang; Yihang Li; Jinzhong Liu; Xiongbin Yang; Xinhong Qi; Xiangcun Li; Gaohong He (Chemical Engineering Journal, 2025)

Dual cryoprotection of gelatin-tea polyphenol microgels on surimi by targeting for ice inhibition and component stabilization - Shichen Zhu; Xuan Wang; Yan Jin; Ningning Peng; Zhengpeng Wei; Jing Lian; Shulai Liu; Yuting Ding; Xuxia Zhou (Food Chemistry, 2025)

Synergistic effect of W(VI) and Ni(II) uptakes on an MgAl-layered double hydroxide - Yili Xie; Xiujuan Yuan; Shichen Liu; Sili Ren; Wuhui Luo (Environmental Research, 2025)

Distribution and air-sea fluxes of CO2 in coral reefs in the Greater Bay Area, China - Hongqiang Yan; Shichen Tao; Lijia Xu; Qi Shi; Yongzhi Wang; Meixia Zhao; Shengnan Zhou; Xiaoju Liu (Regional Studies in Marine Science, 2024)

The history of the El Niño–Southern Oscillation and sea surface salinity during 1376–1500 CE reconstructed by Porites coral δ18O from Huangyan Island, South China Sea - Shichen Tao; Kam-biu Liu; Hongqiang Yan; Min Meng; Kefu Yu; Qi Shi; Huiling Zhang (Global and Planetary Change, 2024)

Visual study of hydrate particles agglomeration and rolling characteristic in gas-oil-water phase using a flow loop - Zheyuan Liu; Shichen Shen; Binlin Dou; Ni Liu; Liang Yang; Mingjun Yang; Yongchen Song (Fuel, 2024)

Cooking-related thermal comfort and carbon emissions assessment: Comparison between electric and gas cooking in air-conditioned kitchens - Jiajun Li; Shichen Li; Yingqi Zeng; Xiang Zhou; Lingjie Zeng; Meng Liu; Changsheng Cao; Yunfei Xia; Jun Gao (Building and Environment, 2024)

Changes in soil microbial community and function across stand age of Cryptomeria japonica var. sinensis plantations in subtropical China - Li Zhang; Shichen Xiong; Ya Shen; Chengming You; Han Li; Lixia Wang; Sining Liu; Bo Tan; Hongwei Xu; Lin Xu; Jiao Li; Zhenfeng Xu (Applied Soil Ecology, 2024)

The OsNAC41-RoLe1-OsAGAP module promotes root development and drought resistance in upland rice - Shichen Han; Yulong Wang; Yingxiu Li; Rui Zhu; Yunsong Gu; Jin Li; Haifeng Guo; Wei Ye; Hafiz Ghualm Nabi; Tao Yang; Yanming Wang; Pengli Liu; et al. (Molecular Plant, 2024)

Genotype of pioneer plant Miscanthus is not a key factor in the structure of rhizosphere bacterial community in heavy metal polluted sites - Danni Liu; Ying-heng Fei; Yuxin Peng; Shichen Zhu; Jianan Lu; Yang Luo; Ziwu Chen; Yuanyuan Jiang; Shizhong Wang; Ye-Tao Tang; Rongliang Qiu; Yuanqing Chao (Journal of Hazardous Materials, 2024)

Myofibrillar protein oxidation associated with surimi processing and emerging control techniques: A review - Hao Zhu; Qingchun Zhang; Yicheng Ding; Shulai Liu; Shichen Zhu; Xuxia Zhou (Trends in Food Science & Technology, 2024)

Improved texture properties and toughening mechanisms of surimi gels by double network strategies - Shichen Zhu; Yingying Wang; Yicheng Ding; Xingwei Xiang; Qing Yang; Zhengpeng Wei; Hua Song; Shulai Liu; Xuxia Zhou (Food Hydrocolloids, 2024)

Investigation on the operating capacity expansion through parallel schemes of reciprocating-switcher energy recovery device for desalination: Simulation, verification and parameterization - Jie Zhou; Dong Liu; Qinghong Zhang; Chao Bian; Xiuxia Meng; Naitao Yang; Shichen Mu (Desalination, 2024)

SST and ENSO activity 282,000 years ago reconstructed from Porites coral in the South China Sea - Shichen Tao; Kam-biu Liu; Hongqiang Yan; Min Meng; Huiling Zhang; Yi Wu; Kefu Yu; Qi Shi (Global and Planetary Change, 2024)

Environmental fate of microplastics in alpine and canyon-type river-cascade reservoir systems: Large-scale investigation of the Yalong River in the eastern Qinghai-Tibet Plateau - Yixuan Liu; Shaoting Zhao; Dongzhi Wang; Shichen Wang; Xiaofan Ding; Kaiyang Han; Ruiying Wang; Yuyang Kou; Guangqian Zhou; Weibo Shen (Science of The Total Environment, 2024)

Using the thiomolybdate-loaded D201 resin derived from the W and Mo separation process as the scavenger of Cr(VI), Cu(II), and Pb(II) - Wuhui Luo; Ting Xiao; Xinhui Jiang; Qianqian Ye; Hongxia Liu; Dandan Gong; Shichen Liu; Sili Ren (Journal of Environmental Chemical Engineering, 2024)

Improving the texture attributes of squid meat (sthenoteuthis oualaniensis) with slight oxidative and phosphate curing treatments - Jiangxiang Wang; Zheng Xu; Wei Lu; Xuxia Zhou; Shulai Liu; Shichen Zhu; Yuting Ding (Food Research International, 2024)

Prostate Cancer, Oxidative Stress, and Antioxidant Phytochemicals: A Brief Review - Shanyi Li; Tong Cai; Shichen Cui; Fangmin Liu; Rong Hu; Wenji Li (Current Pharmacology Reports, 2023)

Expandable polystyrene waste modified iron sludge-based biochar activating multiple free radicals for deep wastewater treatment - Shenglin Bu; Wenzong Liu; Muhammad Rizwan Haider; Xiqi Li; Wenzhe Zhang; Qi Sun; Qiandi Wang; Yuanqiang Guo; Shichen Nie; Aijie Wang (Process Safety and Environmental Protection, 2023)

A comparative study on the taste quality of Mytilus coruscus under different shucking treatments - Shichen Zhu; Lin Zhu; Zhigang Ke; Hui Chen; Yadan Zheng; Peng Yang; Xingwei Xiang; Xiaomin Zhou; Youding Jin; Shanggui Deng; Xuxia Zhou; Yuting Ding; et al. (Food Chemistry, 2023)

Coral growth over the past 550 years in the central South China Sea linked to monsoon- and seabird-induced nutrient stress - Yi Liu; Shichen Tao; Ruoyu Sun; Chen-Feng You; Tzu-Hao Wang; Thomas Felis; Wang Zheng; Shaobo Sun; Xiaodong Liu; Qi Shi; Jianxin Zhao; Kefu Yu (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

Performance characteristics and bacterial community analysis of a novel two-step-feed three-stage A/O-MBBR system for nitrogen removal in municipal wastewater - Xiaolin Zhou; Zijian Jiang; Jinzhao Gu; Xuejun Bi; Jingmiao Liu; Xuyi Wang; Tang Yang; Xueqing Shi; Lihua Cheng; Shujuan Huang; Xiaodong Wang; Harsha Ratnaweera; et al. (Journal of Water Process Engineering, 2023)

Mechanisms of alkali pH-shifted colour changes in squid (Uroteuthis edulis) subjected to frozen storage - Zheng Xu; Yunyun Chen; Xuxia Zhou; Shulai Liu; Jing Xie; Wangli Dai; Shichen Zhu; Yuting Ding (Food Chemistry, 2023)

A novel protein domain is important for photosystem II complex assembly and photoautotrophic growth in angiosperms - Wei Li; Jiangfan Guo; Xue Han; Xiaowen Da; Kai Wang; Hongfei Zhao; Shi-Tang Huang; Bosheng Li; Hang He; Ruirui Jiang; Shichen Zhou; Peng Yan; et al. (Molecular Plant, 2023)

Glucose metabolism patterns: A potential index to characterize brain ageing and predict high conversion risk into cognitive impairment - Jiehui Jiang; Can Sheng; Guanqun Chen; Chunhua Liu; Shichen Jin; Lanlan Li; Xueyan Jiang; Ying Han; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2022)

Localization of QTL for cold tolerance at the germination stage of rice (Oryza sativa L.) using recombinant inbred lines - Liangzi Cao; Shukun Jiang; Guohua Ding; Tongtong Wang; Liangming Bai; Jinsong Zhou; Yu Luo; Tianshu Xia; Hui Jiang; Kai Liu; Xueyang Wang; Guang Yang; et al. (Genetic Resources and Crop Evolution, 2022)
The cold tolerance of germinating direct-sown rice ( Oryza sativa L.) has an increased rate of emergence, which ensures vigorous seedling growth. Research on QTL localization for cold tolerance at the germination stage can assist in molecular marker-assisted selection and enhance breeding efficiency. In this study, 94 populations of recombinant self-incompatible lines from Heigu and Ha 9366 were selected to investigate germination rates at low temperatures. It was found that two QTL loci (qLTG-3 and qLTG-12) were located at different germination times on chromosomes 3 and 12, respectively. The two QTLs at three different germination times, located using QTL, accounted for 21.3–25.9% of the phenotypic variation. Moreover, a reciprocal effect was detected between the two QTLs. The double QTLs increased the germination rate by 22–27% in this population. Additionally, qLTG-12 improved cold tolerance at the seedling stage. The results of this study might provide the materials and molecular markers for future molecular marker-assisted breeding for cold tolerance at the germination stage.

Identification of candidate genes for panicle length in Oryza sativa L. ssp. japonica via genome-wide association study and linkage mapping - Hongliang Zheng; Shichen Sun; Liangming Bai; Shukun Jiang; Guohua Ding; Tongtong Wang; Hongwei Zhao; Jingguo Wang; Hualong Liu; Luomiao Yang; Yan Jia; Xin Wei; et al. (Euphytica, 2022)

Identification and molecular mapping of the semi-dwarf locus (sdf-1) in soybean by SLAF-seq method - Zhimin Dong; Liang Chen; Zhi Li; Nianxi Liu; Shichen Zhang; Jia Liu; Baoquan Liu (Euphytica, 2020)

Tissue-derived scaffolds and cells for articular cartilage tissue engineering: characteristics, applications and progress - Xuejian Liu; Haoye Meng; Quanyi Guo; Baichuan Sun; Kaihong Zhang; Wen Yu; Shichen Liu; Yu Wang; Xiaoguang Jing; Zengzeng Zhang; Jiang Peng; Jianhua Yang (Cell and Tissue Research, 2018)

Development and validation of KASP markers for the greenbug resistance gene Gb7 and the Hessian fly resistance gene H32 in wheat - Chor-Tee Tan; Hangjin Yu; Yan Yang; Xiangyang Xu; Mingshun Chen; Jackie C. Rudd; Qingwu Xue; Amir M. H. Ibrahim; Lisa Garza; Shichen Wang; Mark E. Sorrells; Shuyu Liu (Theoretical and Applied Genetics, 2017)

Interseasonal and interspecies diversities of Symbiodinium density and effective photochemical efficiency in five dominant reef coral species from Luhuitou fringing reef, northern South China Sea - Lijia Xu; Kefu Yu; Shu Li; Guohui Liu; Shichen Tao; Qi Shi; Tianran Chen; Huiling Zhang (Coral Reefs, 2017)

A fractionation procedure for identifying novel proteins induced by chill stress in Arabidopsis thaliana - Liwen Sun; Shichen Wang; Jinghui Xi; Shuo Yang; Xiangguo Liu; Xin Chai; Hongbao Xin; Baiyi An; Dongyun Hao (Biotechnology Letters, 2009)